Structural Determinants of Drug Partitioning in Surrogates of Phosphatidylcholine Bilayer Strata - Lukacova, Viera (2013)
The knowledge of drug concentrations in bilayer headgroups, core, and at the interface between them is a prerequisite for quantitative modeling of drug interactions with many membrane-bound transporters, metabolizing enzymes and receptors, which have the binding sites located in the bilayer. This knowledge also helps understand the rates of trans-bilayer transport because balanced interactions of drugs with the bilayer strata lead to high rates, while excessive affinities for any stratum cause a slowdown. Experimental determination of bilayer location is so tedious and costly that the data are only available for some fifty compounds. To extrapolate these valuable results to more compounds at a higher throughput, surrogate phases have been used to obtain correlates of the drug affinities for individual strata. We introduced a novel system, consisting of a diacetyl phosphatidylcholine (DAcPC) solution with the water content of the fluid bilayer as the headgroup surrogate and n-hexadecane (C16) representing the core. The C16/DAcPC partition coefficients were measured for 113 selected compounds, containing structural fragments that are frequently occurring in approved drugs. The data were deconvoluted into the ClogP-based fragment solvation characteristics and processed using a solvatochromic correlation. Increased H-bond donor ability and excess molar refractivity of compounds promote solvation in the DAcPC phase as compared to bulk water, contrary to H-bond acceptor ability, dipolarity/polarizability, and volume. The results show that aromates have more balanced distribution in bilayer strata, and thus faster trans-bilayer transport, than similar alkanes. This observation is in accordance with the frequent occurrence of aromatic rings in approved drugs and with the role of rigidity of drug molecules in promoting intestinal absorption. Bilayer locations, predicted using the C16/DAcPC system, are in excellent agreement with available experimental data, in contrast to other surrogate systems.